Acute‐on‐chronic liver failure in India: The Indian National Association for Study of the Liver consortium experience. Issue 10 (October 2016) - ,; Saraswat, Vivek; Singh, Shivaram P; Duseja, Ajay; Shukla, Akash; Eapen, Chundamannil E; Kumar, Dharmendra; Pandey, Gaurav; Venkataraman, Jayanti; Puri, Pankaj; Narayanswami, Krishnasamy; Dhiman, Radha K; et al.
Abstract: Background and Aim: The aim of this study was to analyze etiologies and frequency of hepatic and extrahepatic organ failures (OFs) and outcome of acute‐on‐chronic liver failure (ACLF) at 10 tertiary centers in India. Methods: In this retrospective study (2011–2014), patients satisfying Asian Pacific Association for the Study of the Liver definition of ACLF were included. Etiology of acute precipitating insult and chronic liver disease and outcomes were assessed. Occurrence and severity of OF were assessed by chronic liver failure‐sequential organ failure assessment score. Results: The mean (±SD) age of 1049 consecutive ACLF patients was 44.7 ± 12.2 years; Eighty‐two percent were men. Etiology of acute precipitants included alcohol 35.7%, hepatitis viruses (hepatitis A, hepatitis B, and hepatitis E) 21.4%, sepsis 16.6%, variceal bleeding 8.4%, drugs 5.7%, and cryptogenic 9.9%. Among causes of chronic liver disease, alcohol was commonest 56.7%, followed by cryptogenic and hepatitis viruses. Predictors of survival were analyzed for a subset of 381 ACLF patients; OF's liver, renal, coagulation, cerebral, respiratory, and failure were seen in 68%, 32%, 31.5%, 22.6%, 14.5%, and 15%, respectively. Fifty‐seven patients had no OF, whereas 1, 2, 3, 4, and 5 OFs were recorded in 126, 86, 72, 28, and 12 patients, respectively. The mortality increased progressively with increasing number of OFs (12.3% with no OF, 83.3% with five OFs). During a median hospital stay of 8 days, 42.6% (447/1049) of patients died. On multivariate analysis by Cox proportional hazard model, elevated serum creatinine (hazard ratio [HR] 1.176), advanced hepatic encephalopathy (HR 2.698), and requirement of ventilator support (HR 2.484) were independent predictors of mortality. Conclusions: Alcohol was the commonest etiology of ACLF. Within a mean hospital stay of 8 days, 42% patients died. OFs independently predicted survival.